The number of wintering phytophages of sugar beet in leaf litter - Makhovskyi, I.; Fedorenko, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The results of taking into account the species composition of phytophages that winter in leaf litter near the sugar beet plantations in the conditions of the Right-bank Forest-Steppe of Ukraine are presented. Among the phytophagous that wintered in the leaf litter and caused harm to the sugar beet crop, beet blisters (Chaetocnema concinna Mrsch.) 3 specimens / m2 and usual beetroot weevil (Asproparthenis (Botynoderes) punctiventris Germ.)) Was found to be 0.13 / m2, and other phytophages and entomophages.